ANALISIS PERBEDAAN REAKSI PASAR SAHAM SEBELUM DAN SESUDAH PENGUMUMAN DAFTAR EFEK SYARIAH DI BURSA EFEK INDONESIA - Bintang Gemilang; Hasan Mukhibad (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
The purpose of this study is to analyze differences in stock market reactions before and after the announcement of the 2019 Sharia Securities List (DES) by the Financial Services Authority (OJK). Market reactions are indicated by differences in share prices which have an impact on the differences in stock returns from before. This is in accordance with the signal theory where there is good news that will be responded to by investors with increasing investor interest in buying these shares, so that the stock return will also increase. The population of this study is all stocks on the Indonesia Stock Exchange in 2019. The sampling method used in this study is the purposive sampling method and produces 78 units of analysis. The data analysis method used was the paired t-test and used the SPSS 25 analysis tool.The results showed that the announcement of the issuance of changes in share status resulted from screening by the Financial Services Authority (OJK) on the Sharia Securities List (DES), there was no difference in stock returns. both in stocks that were previously conventional to become sharia and stocks that were originally sharia to become conventional. In addition, Islamic stocks have a greater difference in return when compared to conventional stocks.